Conte, Jean le teigneux. Suite de l'enregistrement inventorié MUS1949.7.9 et MUS1949.7.10 - zk51vh138; xw42n835f (k930bx43m; 9306sz60j, 1949)
Description analytique : Conte, Jean le teigneux. Suite de l'enregistrement inventorié MUS1949.7.9 et MUS1949.7.10